Effectiveness of Drugs Therapy of Hypertensive Patients in Undata General Hospital Palu - Ingrid Faustine (Journal of Global Pharma Technology, 2020)
Increased blood pressure above normal will result in increased morbidity and mortality by improving risk factor for other diseases. Data obtained from Undata General Hospital Palu, showed the number of hypertensive patients died in 2016 as many as 513 patients, this number increased in 2017 as many as 637 patients. This study aims to determine the accuracy of the selection of antihypertension therapy and dose as well as determine the effect of antihypertension drugs to decrease blood pressure in hypertensive patients in hozpitalized Undata Generala Hospital Palu in 2016-2017. This study uses a quantitative method with retrospective approach. The results showed that the most significant decrease in blood pressure based on length of stay occurred in patients with 4-7 days of stay ie 42.64/21.17 mmHg and the most significant reduction in blood pressure based on the treatment regimen occurred in three combination antihypertension 57.14/28.57 mmHg with a significance value of<0.05. So we concluded the accuracy of therapy and dose in hypertensive patients based on the guidelines JNCVII showed a patient diagnosed with mild, moderate, and severe hypertension overall proper drug selection and dose received by all patients with hypertension better use of antihypertension drugs singly or in combination in accordance with the standards of the JNCVII, and paired t-test for hypertensive patients with a single drug decreased blood pressure 37.80/16.19 mmHg (p=<0.05), hypertensive patients with two combinations of drugs decreased blood pressure 29.26/18.94 mmHg (p=<0.05) and hypertensive patients with three combinations of drugs decreased blood pressure 57.14/28.5 mmHg (p=<0.05).Keywords: Effectivenes, Drugs Therapy, Undata General Hospital, Hypertension.